Concurrent Changes in 24-Hour Movement Behaviors and Cognitive Function during Retirement Transition: Longitudinal Compositional Data Analysis - Palmberg, Lotta; Suorsa, Kristin; Leskinen, Tuija; Pasanen, Jesse; Rovio, Suvi; Stenholm, Sari (Lippincott Williams and Wilkins, 2026)
Background: Transitioning to retirement may change physical activity, sedentary behavior, and sleep, i.e., 24-h movement behaviors, but it is unknown whether these changes are linked to cognitive function. This study investigates the longitudinal associations between changes in 24-h movement behaviors and cognitive function during the retirement transition.
Methods: Study population consisted of public sector workers (n = 147, mean age 63.3 years, SD 1.0) from the Finnish Retirement and Aging study. A thigh-worn Axivity accelerometer was used to estimate daily time in sleep, sedentary behavior (SED), light physical activity (LPA) and moderate-to-vigorous physical activity (MVPA) before and after retirement (one year in-between). Similarly, computerized Cambridge Neuropsychological Test Automated Battery was conducted repeatedly to evaluate six cognitive domains: learning and memory, working memory, sustained attention and information processing, executive function and cognitive flexibility, and reaction time. Associations between changes in 24-h movement behaviors and cognitive function were analyzed using compositional linear regression and isotemporal substitution analyses.
Results: An increase in active (LPA and MVPA) relative to passive behaviors (sleep and SED) and SED relative to sleep were associated with improvement in reaction time (βilr = 0.21, p = 0.04, βilr = 0.55, p = 0.02). Especially reallocating time from sleep to other behaviors showed positive associations. For instance, reallocating 30 min from sleep to other behaviors was associated with 0.05 standardized unit improvement in reaction time. No associations between changes in movement behaviors and changes in any other cognitive domain were observed.
Conclusions: Reallocating time from sleep to other behaviors during retirement transition was associated with improvement in reaction time. Further studies are needed to examine long-term consequences of changes in 24-h movement behaviors for cognitive function.